Effects of Social Media in Tourism Marketing: Outlook on User Generated Content - Deb, Santus Kumar; Mallik, Nandita (Tecno Scientifica Publishing, 2023)
Social media has transformed the tourism industry, shifting it from its conventional model into an extreme knowledge pattern. This study focuses on the use of social media for tourism marketing to enhance tourist satisfaction through user-generated content. A mixed research method was employed, with an exploratory approach used to identify the critical success factors of social media user-generated content (UGC) for marketing tourism products. Purposive sampling was utilized, and data were collected from 200 respondents. To analyze the data, frequency distribution, multiple regression, and hypothesis testing were employed for user-generated content on social media for tourism marketing. The results of the study reveal that people spend an average of one to six hours daily on social media platforms. Graduate students aged 21-30 and employed individuals are more likely to use social media for travel purposes. The study also indicates that factors such as advocacy, a positive brand impression, travel inspiration, and careful content development are crucial for social media in tourism marketing. The travel industry provides visitors with personalized services, offering a social media network that systematically shares users' and like-minded people's experiences, allowing users to customize their anonymity and add value to their personal details.